Pengendalian Laju Korosi Baja AISI 1018 Dalam Medium Korosif NaCl 3% Menggunakan Inhibitor Ekstrak Daun Ketapang (Terminalia catappa L.) - Ulfa Nurini; Ediman Ginting Suka; Roniyus Marjunus (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2022)
This research aims to determine the effectiveness of ketapang leaf extract (Terminalia catappa L.) as inhibitor on AISI steel in corrosive medium NaCl 3%. Specifically, the purpose of this research is to know the effect of the addition of 0%, 2%, 4%, 6%, 8%, dan 10% inhibitor concentration of ketapang leaf extract and 6 days to the corrosion rate. To find out the corrosion rate resulted by weight reduction method with an inhibitor efficiency value of 69,9%. The x-ray diffraction (XRD) results show that the phase formed is pure Fe phase. The results of scanning electron microscopy (SEM) show the presence of lumps on steel surfaces of various sizes which are the product of corrosion. This is reinforced by the results of energy dispersive spectroscopy (EDS) which shows that the increasing number of lumps on the steel surface leaves fewer Fe elements.